Optimalaisasi Peran dan Fungsi Pemerintahan Desa di Kabupaten Bolaang Mongondow Selatan - Ramli Madjid; Arifin Tahir; Titin Dunggio (LP2M Universitas Bina Mandiri Gorontalo, 2022)
The objectives of this research are: (1) Knowing and analyzing the optimization of the roles and functions of village government. (2) Knowing and analyzing the factors that determine and hinder the optimization of the role and function of the village government. This research is a research with a qualitative descriptive approach, namely examining, analyzing and decrypting the data. The informants in this study were 33 people consisting of: Camat, District Secretary, Head of BPD, Sangadi, Village Secretary, Head of Financial Affairs, and Head of Government Section. Research Results: (1) The roles and functions of local government have been optimal. For the role of the village government in the implementation of government in the village, both as a dynamist, catalyst, and pioneer, it has been going well or has been optimal based on the results of interviews that have been conducted. Meanwhile, the function of the village government is in development planning, village government administration; and Village financial management, has been running well or has been optimal based on the results of interviews that have been conducted; (2) Government policy factors that most influence the optimization of village government roles and functions, with the consideration that human resources (apparatus), budget (finance), facilities and infrastructure all depend on government policies (central, provincial and district). Suggestions: (1) In order to optimize the roles and functions of the village government, a higher quality of human resources is needed. (2) The government can provide future policies regarding the functions and roles of village government.